The Effect of Tourism Infrastructure Asset Quality on Tourist Satisfaction: A Case on Forest Tourism in Tasikmalaya Regency - Aceng Gima Sugiama; Husna Candranurani Oktavia; Monik Karlina (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2022)
This study aims to determine the effect of the quality of tourism infrastructure assets on tourist satisfaction on forest tourism in Tasikmalaya Regency including the quality of accommodation, quality of accessibility and quality of amenities. The research population is tourists who have visited the Batu Hanoman Waterfall, Batu Blek Waterfall, Candung Waterfall, and Ciparay Waterfall in Tasikmalaya Regency with a sample size of 336 respondents, applying a purposive sample. The data is processed using the Structural Equation Model (SEM). The results of this study indicate that the quality of accommodation, the quality of accessibility and the quality of amenities have a positive effect on tourist satisfaction. This means that tourism infrastructure assets, both quality of accommodation, quality of accessibility and quality of amenities can increase satisfaction for tourists. In total, the quality of amenities has the greatest influence on tourist satisfaction, followed by the quality of accessibility and quality of accommodation. Studies prove that efforts to increase tourist satisfaction can be done by improving the quality of accommodation, quality of accessibility, and quality of amenities.